2001
DOI: 10.1001/archopht.119.12.1827
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factors for Pterygium in the Barbados Eye Study

Abstract: To describe the distribution and risk factors for pterygium in the predominantly black population of the Barbados Eye Study, which was based on a random sample of Barbadian-born citizens between the ages of 40 and 84 years. Methods: The standardized protocol included ophthalmic and other measurements, automated perimetry, lens gradings, fundus photography, and a detailed interview. A 10% systematic sample of participants and those meeting specific criteria also received a comprehensive ophthalmologic evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
150
3
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(174 citation statements)
references
References 29 publications
14
150
3
7
Order By: Relevance
“…26 The survey found that the participants who seldom use sunglasses and/or wear a hat when they are outside had a positive association to pterygium (OR 1.5; 95% CI, 1.2, 1.9 and OR 1.3; 95% CI, 1.1, 1.7, respectively). This result was similar to the Barbados Eye Study 23 and Rosenthal et al 30 We believe the protective mechanism is related to the ability of glasses and a hat to block ultraviolet-B wavelengths of sunlight or to shield the eye from other harmful environmental exposures, since hazardous environmental factors play a very important role in pterygium formation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…26 The survey found that the participants who seldom use sunglasses and/or wear a hat when they are outside had a positive association to pterygium (OR 1.5; 95% CI, 1.2, 1.9 and OR 1.3; 95% CI, 1.1, 1.7, respectively). This result was similar to the Barbados Eye Study 23 and Rosenthal et al 30 We believe the protective mechanism is related to the ability of glasses and a hat to block ultraviolet-B wavelengths of sunlight or to shield the eye from other harmful environmental exposures, since hazardous environmental factors play a very important role in pterygium formation.…”
Section: Discussionsupporting
confidence: 88%
“…21 The prevalence of pterygium among 477 residents on a tropical island in Indonesia, however, was high, at 17.0%, 22 and the black population of the Barbados Eye Study was even higher, 23.4% of 2617 participants were aged 40-84 years. 23 The highest prevalence of pterygium, to our knowledge, was in subjects aged 50 years or above in a rural area of southern China, 33.01%. 10 In HES, we found the prevalence of pterygium was 13.5 (95% CI, 11.2, 15.9) in participants aged 40-49, but 27.5% (95% CI, 15.2, 39.7) for those aged 80 and above.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The prevalence rates of pterygium reported in different studies vary considerably (0.35-31.1%) [1][2][3][4][5][6] and may be affected by factors such as age, 6,7 gender, [6][7][8] ultraviolet (UV) radiation exposure, [7][8][9][10][11] and time spent outdoors. 1,3,12,13 Our study aimed to describe the epidemiology of pterygium among residents of a tropical island in Indonesia and to examine the roles of age and gender as determinants of bilaterality and severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of pterygium is still uncertain, some risk factors including ultraviolet (UV) exposure, [9][10][11][12] age, 1,11 race, 13 and family history 14 have been proposed. Among these risk factors, UV exposure has been documented to have strong correlation with pterygium, but the mechanism by which UV light induces pterygium remains elusive.…”
Section: Introductionmentioning
confidence: 99%